MAPLE APPLICATION TRAINING PROGRAM FOR MATHEMATICS EDUCATION AT UNIVERSITAS KATOLIK SANTO AGUSTINUS HIPPO - Bernadeta Ritawati; Nasri Tupulu; Konstansia Hermiati; Pradipta Annurwanda (Yayasan Education and Social Center, 2023)
The community service activity entitled “Maple Application Training for Mathematics Education Study Program” at St. Augustine Hippo Catholic University aims to improve students' abilities in mathematics education study programs using existing applications as sources of learning mathematics. The problems found at the Catholic University of St. Augustine Hippo in the mathematics education study program where students still do not know the application, students still use the manual way of counting, students are still not accustomed to using existing learning applications, and rarely use applications in learning. Community service activities that use a participatory approach and through this training method, the result that students at St. Augustine Hippo Catholic University realized that increasing competence is essential for the world of education, both in increasing knowledge and skills, through various applications of learning mathematics, in this case, the application of maple. Educators here can improve their competence to play a direct role in online and offline learning to improve students' mathematical problem-solving abilities.